Local religion in North China in the twentieth century : the structure and organization of community rituals and beliefs - Overmyer, Daniel L., 1935- (Handbuch der Orientalistik. China, 2009)
"This book is a comprehensive survey of the structure, organization and institutionalization of local community religious traditions in north China villages in the twentieth century. These traditions have their own forms of leaders, deities and beliefs. Despite much local variation one everywhere finds similar temples, images, offerings and temple festivals, all supported by practical concerns for divine aid to deal with the problems of everyday life. These local traditions are a structure in the history of Chinese religions; they have a clear sense of their own integrity and rules, handed down by their ancestors. There are Daoist, Buddhist and government influences on these traditions, but they must be adapted to the needs of local communities. It is the villagers who build temples and organize festivals, in which all members of the community are expected to participate and contribute. With chapters on such topics as historical origins and development, leadership and organization, temple festivals, temples and deities, and beliefs and values."--Jacket